Case report: From anxiety disorders to psychosis, a continuum in transitional age youth? - Reis, Joana; Marchini, Simone; Nicolis, Hélène; Delvenne, Véronique (Frontiers in Psychiatry, 2022)
Introduction To date, among individuals meeting ultra-high risk criteria for psychosis, the relationship between the presence of anxiety disorders and the risk of psychotic transition raises several unanswered questions. Case description This case report describes the clinical progression of a 17-year-old male initially presenting anxious symptoms meeting the DSM-V criteria for panic disorder. The patient also reported social withdraw, mild depressive symptoms, insomnia and fatigue. Over a 6 month period, a gradual onset of subthreshold psychotic symptoms suggested a prodromal phase of a psychotic disorder. Diagnostic assessment and therapeutic intervention A detailed assessment of UHR criteria for psychosis was performed. The overall level of social and occupational functioning was assessed by the SOFAS, which showed a 35% drop over a 12 months period. The CAARMS, has also been administered. The patient met the diagnostic criteria for UHR, APS group. The care plan included psychiatric follow-up, pharmacologic treatment, individual psychological follow-up and individual and familial psychoeducation. Over a 6 months period, the patient did not experienced a first psychotic episode and presented a partial improvement of psychotic symptoms. Conclusion The DSM-V categorical approach does not seem to adapt well to early clinical presentations in transitional age youth. A transdiagnostic and dimensional approach allows to better identify at-risk patients of psychiatric disorders and implement early intervention strategies.